TOTAL MOTİL SPERM SAYISININ İNTRAUTERİN İNSEMİNASYON BAŞARISINA ETKİSİ - ALICI, Bülent; ÖZKARA, Hamdi; ÖNAL, Bülent; AKKUŞ, Emre; HATTAT, Halim (Cerrahpaşa Medical Journal, 2014)
Background and Design.- In our clinic, 162 couples underwent 421 cycles of intrauterine insemination (IUI) with male factor infertility but normal female findings. The purpose of this study was to evaluate the relationship between the total motile sperm count and the success of intrauterine insemination. Results.- Twenty-two of 24 pregnancies had occurred in the group which underwent 289 cycles of IUI with total motile sperm count more than 5 million/cc. On the other hand only two pregnancies were obtained in the group which underwent 132 cycles of IUI with total motile sperm count less than 5 million/cc. Statistical significance was present in success of IUI between groups with total motile sperm count less than and more than 5 million/cc ('x2= 6.27, p< 0.01). Conclusion.- Post washed total motile sperm count may be considered as a predictive criteria of the success for pregnancy in couples with male factor infertility.